PENCARIAN FILE DENGAN METODE BINARY SEARCHING DAN DENGAN PENDEKATAN WILDCARD CHARACTER - Budi Yanto, Erni Rouza (RJOCS (Riau Journal of Computer Science), 2017)
Information technology and the growing and sophisticated should be balanced according to need. Therefore, the authors designed a Software Search File With Binary Search method. Many methods in the search with the aim of facilitating the search in the future, such as searching file with binary search method and improve Wildcard Character..